2017
DOI: 10.1093/bioinformatics/btx408
|View full text |Cite
|
Sign up to set email alerts
|

Partitioned learning of deep Boltzmann machines for SNP data

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Subsequently, new, synthetic samples can be generated that represent what kind of biological structure has been uncovered. We focus on Deep Boltzmann Machines (DBMs) (Srivastava and Salakhutdinov, 2014) because these allow for flexible conditional sampling, and we have already adapted them for training with small sample sizes (Hess et al, 2017). While our previous approach was primarily designed for handling genetic data, our Julia package "BoltzmannMachines" now can integrate data of different types, i.e.…”
Section: Motivationmentioning
confidence: 99%
“…Subsequently, new, synthetic samples can be generated that represent what kind of biological structure has been uncovered. We focus on Deep Boltzmann Machines (DBMs) (Srivastava and Salakhutdinov, 2014) because these allow for flexible conditional sampling, and we have already adapted them for training with small sample sizes (Hess et al, 2017). While our previous approach was primarily designed for handling genetic data, our Julia package "BoltzmannMachines" now can integrate data of different types, i.e.…”
Section: Motivationmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, the model assumptions underlying these models, such as the proportional hazard, independence between censoring and survival times, linearity in coefficients, may not be tenable in real applications. For this reason, nonparametric approaches such as neural networks [7][8][9] can be useful alternatives. In particular, neural networks methodology has been adapted to survival analysis for more than two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the structural simplicity and its popularity, several machine learning methods including the popular deep neural networks have been extended to Cox's regression analysis in conjunction with the Faraggi-Simon method. [7][8][9][22][23][24] But perhaps due to the computation burden incurred by the backpropagation algorithms that are widely employed in both multilayer perceptron (MLP) neural networks and deep neural networks, most of these proposals focus on low-dimensional survival data. These sophisticated deep learning methods have demonstrated their usefulness in high-dimensional setting.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have considered using deep learning for genotype-phenotype association studies. Most approaches first reduced the number of variants included in the model either by selecting variants that were known to be associated with disease (Uppu and Krishna, 2017;Hess et al, 2017), or by preselecting those variants that showed a sufficiently strong correlation with phenotype in a regular GWAS (Montañez et al, 2018b;Bellot et al, 2018). Two studies combine the latter strategy with the use of autoencoders for further dimensionality reduction (Montañez et al, 2018a;Fergus et al, 2018).…”
Section: Introductionmentioning
confidence: 99%